Progress in Stem Cell Therapy for Spinal Cord Injury - Liansheng Gao; Yucong Peng; Weilin Xu; Pingyou He; Tao Li; Xiaoyang Lu; Gao Chen (Hindawi Limited, 2020)
Background. Spinal cord injury (SCI) is one of the serious neurological diseases that occur in young people with high morbidity and disability. However, there is still a lack of effective treatments for it. Stem cell (SC) treatment of SCI has gradually become a new research hotspot over the past decades. This article is aimed at reviewing the research progress of SC therapy for SCI. Methods. Review the literature and summarize the effects, strategies, related mechanisms, safety, and clinical application of different SC types and new approaches in combination with SC in SCI treatment. Results. A large number of studies have focused on SC therapy for SCI, most of which showed good effects. The common SC types for SCI treatment include mesenchymal stem cells (MSCs), hematopoietic stem cells (HSCs), neural stem cells (NSCs), induced pluripotent stem cells (iPSCs), and embryonic stem cells (ESCs). The modes of treatment include in vivo and in vitro induction. The pathways of transplantation consist of intravenous, transarterial, nasal, intraperitoneal, intrathecal, and intramedullary injections. Most of the SC treatments for SCI use a number of cells ranging from tens of thousands to millions. Early or late SC administration, application of immunosuppressant or not are still controversies. Potential mechanisms of SC therapy include tissue repair and replacement, neurotrophy, and regeneration and promotion of angiogenesis, antiapoptosis, and anti-inflammatory. Common safety issues include thrombosis and embolism, tumorigenicity and instability, infection, high fever, and even death. Recently, some new approaches, such as the pharmacological activation of endogenous SCs, biomaterials, 3D print, and optogenetics, have been also developed, which greatly improved the application of SC therapy for SCI. Conclusion. Most studies support the effects of SC therapy on SCI, while a few studies do not. The cell types, mechanisms, and strategies of SC therapy for SCI are very different among studies. In addition, the safety cannot be ignored, and more clinical trials are required. The application of new technology will promote SC therapy of SCI.